California Planting Cotton Seed Distributors Miscellaneous Files 1959-1961 - California Planting Cotton Seed Distributors
Item contains miscellaneous files including but not limited to: • Ranchers Planting Seed Committee Report • July 1960 Audit of the CPCSD • Special Directors Meeting • 1959-1960 Seed Data